\(\sqrt{\left(\sqrt{3}-2\right)^2}+\sqrt{12}-\sqrt{\left(-3...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 11 2018

\(A=\sqrt{\left(\sqrt{3}-2\right)^2}+\sqrt{12}-\sqrt{\left(-3\right)^2}\)

\(=|\sqrt{3}-2|+2\sqrt{3}-|-3|\)

\(=2-\sqrt{3}+2\sqrt{3}-3\)

\(=\sqrt{3}-1\)

=.= hok tốt!!

26 tháng 7 2018

Giup mình phần 3,4,5 của bài 2 với bài 4 nữa . Helpppp me !!

26 tháng 10 2020

a) \(\sqrt{\left(\sqrt{3}-2\right)^2}+\sqrt{12}-\sqrt{\left(-3\right)^2}\)

\(=\left|\sqrt{3}-2\right|+\sqrt{2^2\cdot3}-\sqrt{3^2}\)

\(=2-\sqrt{3}+2\sqrt{3}-3\)

\(=\sqrt{3}-1\)

b) \(\left(\sqrt{8}-3\sqrt{6}+\sqrt{2}\right)\cdot\sqrt{2}+\sqrt{108}\)

\(=\sqrt{16}-3\sqrt{12}+\sqrt{4}+\sqrt{6^2\cdot3}\)

\(=4-3\sqrt{2^2\cdot3}+2+6\sqrt{3}\)

\(=6-3\cdot2\sqrt{3}+6\sqrt{3}\)

\(=6-6\sqrt{3}+6\sqrt{3}=6\)

26 tháng 10 2020

a) \(\sqrt{\left(\sqrt{3}-2\right)^2}+\sqrt{12}-\sqrt{\left(-3\right)^2}\)

\(=\left|\sqrt{3}-2\right|+\sqrt{3.4}-\sqrt{3^2}=2-\sqrt{3}+\sqrt{4}.\sqrt{3}-3\)

\(=2-\sqrt{3}+2\sqrt{3}-3=\sqrt{3}-1\)

b) \(\left(\sqrt{8}-3\sqrt{6}+\sqrt{2}\right).\sqrt{2}+\sqrt{108}\)

\(=\sqrt{8}.\sqrt{2}-3\sqrt{6}.\sqrt{2}+\sqrt{2}.\sqrt{2}+\sqrt{108}\)

\(=\sqrt{8.2}-3\sqrt{6.2}+2+\sqrt{36.3}\)

\(=\sqrt{16}-3\sqrt{12}+2+\sqrt{36}.\sqrt{3}\)

\(=\sqrt{4^2}-3\sqrt{4.3}+2+6\sqrt{3}\)

\(=4-3\sqrt{4}.\sqrt{3}+2+6\sqrt{3}\)

\(=4-6\sqrt{3}+2+6\sqrt{3}=6\)

11 tháng 7 2018

Bài 1:

a)  \(\frac{2}{\sqrt{3}-1}-\frac{2}{\sqrt{3}+1}\)

\(=\frac{2\left(\sqrt{3}+1\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}-\frac{2\left(\sqrt{3}-1\right)}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}\)

\(=\frac{2\left(\sqrt{3}+1\right)}{2}-\frac{2\left(\sqrt{3}-1\right)}{2}\)

\(=\sqrt{3}+1-\left(\sqrt{3}-1\right)=2\)

b)   \(\frac{2}{5-\sqrt{3}}+\frac{3}{\sqrt{6}+\sqrt{3}}\)

\(=\frac{2\left(5+\sqrt{3}\right)}{\left(5-\sqrt{3}\right)\left(5+\sqrt{3}\right)}+\frac{3\left(\sqrt{6}-\sqrt{3}\right)}{\left(\sqrt{6}+\sqrt{3}\right)\left(\sqrt{6}-\sqrt{3}\right)}\)

\(=\frac{2\left(5+\sqrt{3}\right)}{2}+\frac{3\left(\sqrt{6}-\sqrt{3}\right)}{3}\)

\(=5+\sqrt{3}+\sqrt{6}-\sqrt{3}=5+\sqrt{6}\)

c)  ĐK:  \(a\ge0;a\ne1\)

  \(\left(1+\frac{a+\sqrt{a}}{1+\sqrt{a}}\right).\left(1-\frac{a-\sqrt{a}}{\sqrt{a}-1}\right)+a\)

\(=\left(1+\frac{\sqrt{a}\left(\sqrt{a}+1\right)}{1+\sqrt{a}}\right).\left(1-\frac{\sqrt{a}\left(\sqrt{a}-1\right)}{\sqrt{a}-1}\right)+a\)

\(=\left(1+\sqrt{a}\right)\left(1-\sqrt{a}\right)+a\)

\(=1-a+a=1\)

1 tháng 10 2020

a) \(\sqrt{\left(5-\sqrt{3}\right)^2}=\left|5-\sqrt{3}\right|=5-\sqrt{3}\)

b) \(\sqrt{\left(1-\sqrt{2}\right)^2}=\left|1-\sqrt{2}\right|=-\left(1-\sqrt{2}\right)=\sqrt{2}-1\)( vì 1 < √2 )

c) \(\sqrt{\left(\sqrt{3}-2\right)^2}=\left|\sqrt{3}-2\right|=-\left(\sqrt{3}-2\right)=2-\sqrt{3}\)( vì √3 < 2 )

b: \(=\left(12\sqrt[3]{2}+2\sqrt[3]{2}-2\sqrt[3]{2}\right)\cdot\left(5\sqrt[3]{4}-3\sqrt[3]{\dfrac{1}{2}}\right)\)

\(=12\sqrt[3]{2}\cdot5\sqrt[3]{4}-12\sqrt[3]{2}\cdot3\sqrt[3]{\dfrac{1}{2}}\)

\(=12\cdot5\cdot2-12\cdot3=120-36=84\)

9 tháng 8 2017

1)   \(\sqrt{\left(1-\sqrt{2}\right)^2}\)\(+\sqrt{\left(\sqrt{2}+3\right)^2}\)

\(=1-\sqrt{2}+\sqrt{2}+3\)

\(=4\)

2) \(\sqrt{\left(\sqrt{3}-2\right)^2}+\sqrt{\left(\sqrt{3}-1\right)^2}\)

\(=\sqrt{3}-2+\sqrt{3}-1\)

\(=2\sqrt{3}-3\)

4 tháng 9 2020

Bài 1:

a)    \(=5.|2a|-5a^2\)

b)    \(=7\left(a-1\right)+5a=12a-7\)

c)    \(|a-2|-5\sqrt{a+2}\)

Bài 2:

a)    \(=3-\sqrt{2}+5-\sqrt{2}=8-2\sqrt{2}\)

b)    \(=3+\sqrt{2}-\left(3-\sqrt{2}\right)\)

\(=2\sqrt{2}\)

c)    \(=6-\sqrt{5}-\left(6+\sqrt{5}\right)\)

\(=-2\sqrt{5}\)

5 tháng 9 2020

a) \(5\sqrt{4a^2}-5a^2\)

\(=5.|2a|-5a^2\)

b) \(7\sqrt{\left(a-1\right)^2}+5a\)

\(=7\left(a-1\right)+5a\)

\(=12a-7\)

c) \(\sqrt{\left(2-a\right)^2}-5\sqrt{a+2}\)

\(=|a-2|-5\sqrt{a+2}\)

bài 2:

a)\(\sqrt{\left(3-\sqrt{2}\right)^2}+\sqrt{\left(\sqrt{2}-5\right)^2}\)

\(=3-\sqrt{2}+5-\sqrt{2}\)

\(=8-2\sqrt{2}\)

b) \(\sqrt{11+6\sqrt{2}}-\sqrt{11-6\sqrt{2}}\)

\(=3+\sqrt{2}-\left(3-\sqrt{2}\right)\)

\(=2\sqrt{2}\)

c)\(\sqrt{41-12\sqrt{5}}-\sqrt{41+12\sqrt{5}}\)

\(=6-\sqrt{5}-\left(6+\sqrt{5}\right)\)

\(=-2\sqrt{5}\)